Stabilization of horseradish peroxidase by covalent conjugation with dextran aldehyde against temperature and pH changes - Altikatoglu, Melda; Arioz, Candan; Basaran, Yeliz; Kuzu, Huriye (DE GRUYTER POLAND SP Z O O, 2009)
Stabilization of Horseradish Peroxidase (HRP; EC 1.11.1.7) against temperature and pH via the formation of the conjugates obtained by multipoint covalent bonding of dextran aldehyde (DA) to the enzyme were studied. Hence, three different molar weighted dextrans (17.5 kD, 75 kD, 188 Q were covalently bonded to purified enzyme with different molar ratios (n(HRP)/n(DA) 20/1, 10/1, 1/1, 1/5, 1/10, 1/15, 1/20). The thermal stabilities of the obtained conjugates were evaluated with the activities determined at different temperatures (25, 30, 35, 40, 50, 60, 70, 80 degrees C) applying 60 minutes incubation time. Conjugates formed were characterized by gel-permeation chromatography (GPC) and fluorescence techniques. The conjugate synthesized using dextran 75 kDa with n(HRP)/n(DA) 1/10 molar ratio showed better thermal stability than other conjugates and purified enzyme at pH 7. This conjugate also has wider activity pH range than purified enzyme. In addition, mentioned conjugate at pH 7 had very long storage lifetime compared to purified enzyme at +4 degrees C and room temperature; which is considered a favorable feature for usage in practice.
Keywords: Enzyme stabilization; Covalent conjugate; Horseradish peroxidase; Dextran; GPC; STABILITY; ENZYMES; INACTIVATION; COMPLEX; THERMOSTABILITY; DEGRADATION; BIOCATALYST; AFFINITY; SURFACE; Chemistry